Study of adsorption process of iron colloid substances on activated carbon by ultrasound; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Machekhina K. I. Ksenia Igorevna; Shiyan L. N. Lyudmila Nikolaevna; Yurmazova T. A. Tatyana Aleksandrovna; Voyno D. A. (2015, 2015)
Title screen